2018
DOI: 10.1186/s13064-018-0111-z
|View full text |Cite
|
Sign up to set email alerts
|

Structural aspects of plasticity in the nervous system of Drosophila

Abstract: Neurons extend and retract dynamically their neurites during development to form complex morphologies and to reach out to their appropriate synaptic partners. Their capacity to undergo structural rearrangements is in part maintained during adult life when it supports the animal’s ability to adapt to a changing environment or to form lasting memories. Nonetheless, the signals triggering structural plasticity and the mechanisms that support it are not yet fully understood at the molecular level. Here, we focus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 149 publications
(156 reference statements)
1
41
0
Order By: Relevance
“…Athreya et al, 2017; Jonas and Kording, 2015; Sporns and Betzel, 2016) might also reveal additional networks structure. It will be of interest to learn whether this community is consistent across individuals, and whether it varies as a function of genetic background, neuronal activity levels, and environmental conditions during development (Kremer et al, 2010; Sugie et al, 2018). Even if the observed network structure is conserved across individuals, it is likely that synaptic output from food-responsive KCs is variable, given that MBON odorant responses are highly variable across individuals (Hige et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Athreya et al, 2017; Jonas and Kording, 2015; Sporns and Betzel, 2016) might also reveal additional networks structure. It will be of interest to learn whether this community is consistent across individuals, and whether it varies as a function of genetic background, neuronal activity levels, and environmental conditions during development (Kremer et al, 2010; Sugie et al, 2018). Even if the observed network structure is conserved across individuals, it is likely that synaptic output from food-responsive KCs is variable, given that MBON odorant responses are highly variable across individuals (Hige et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Many animals, including humans, exhibit brain plasticity over the course of their lifetime (May, ; Nava and Röder, ; Harris et al , ). Plasticity is widespread even at the adult stage in insects (Fahrbach and Van Nest, ; Fahrbach et al , ; Simões and Rhiner, ; Sugie et al , ). In adult insects, one brain region that exhibits plasticity is the mushroom body (MB).…”
Section: Introductionmentioning
confidence: 99%
“…Landmark studies in kittens have shown that depriving them of visual input during an early critical period by suturing their eyelids permanently impaired their vision, even after their eyes were opened again (Hubel and Wiesel, 1964). Activity can refine the patterns of connections through Hebbian and/or homeostatic plasticity mechanisms (Kaneko et al, 2017;Marder, 2011;Schulz and Lane, 2017;Sheng et al, 2018;Sugie et al, 2018;Tien and Kerschensteiner, 2018;Tripodi et al, 2008;Turrigiano, 2017;Yuan et al, 2011). However, what kinds of changes are induced within the network in response to selective silencing of specific neuron types is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…This raises the possibility that neuronal activity between 28 developing neurons might contribute to wiring specificity (Akin et al, 2019), in addition to specific partner--derived molecular cues. Despite extensive work investigating the role of activity in circuit formation, it is still unclear whether activity is involved in partner specificity (Kaneko and Ye, 2015;Sugie et al, 2018).…”
Section: Lack Of Chordotonal Activity During Development Alters Connementioning
confidence: 99%
See 1 more Smart Citation